Comparative Histomorphological and Histochemical studies on Magnum of Oviduct of Jharseem and Dahlem Red Hen - Ahmad, Mohammad Taufique (Indian Journal of Veterinary Anatomy, 2020)
The present investigation showed that the lamina epithelialis of Jharseem and Dahlem Red was made up of pseudostratified ciliated columnar cells with few goblet cells. In Jharseem birds the goblet cells were few, mucosal folds were usually conical in shape and lamina propria-submucosa was compact. Whereas, in Dahlem Red birds the mucosal folds were finger like in shape. In Jharseem birds the number of mucosal folds were comparatively more than that of Dahlem Red birds In Jharseem the lamina epithelialis of magnum showed strong positive reaction for PAS and moderate for bromphenol blue. However, in Dahlem red birds it showed strong affinity for PAS and moderate for bromphenol blue. In Jharseem the tubular glands of magnum showed weak positive reaction for PAS but moderate for bromphenol blue. However, in Dahlem Red hens the tubular glands showed very strong reaction for bromophenol blue and strong reaction for PAS.